Ekstrak Daun Ketapang (Terminalia Catappa) Sebagai Larvasida Alami - Dwi Yuliani; Desi Safitri; Putra Firman Suci Adi (JURNAL ILMIAH ULTRAS BREBES, 2023)
Dengue Hemorrhagic Fever (DHF) is still one of the health problems in Indonesia. The disease that emerged since 1968 has claimed many victims in various regions and until now. Vector control using chemical larvicides has many resistant effects on these larvicides. One option to avoid this requires natural larvicides. Therefore, the purpose of this study was to provide information on the potential of Ketapang leaf extract (Terminalia Catapppa) as a natural larvicide against the mortality of Aedes aegypti mosquito larvae. The method of making Ketapang leaf extract (Terminalia Catappa) is steam distillation. The results of the steam distillation in the form of Ketapang leaf extract were then tested to determine the effectiveness of the ketapang leaf extract as a natural larvicide on the mortality rate of Aedes aegypti mosquito larvae. The effectiveness test on the mortality of Aedes aegypti mosquito larvae was carried out by conducting a control test and adding Ketapang leaf extract (Terminalia Catappa) with various formulas and time variations. The results obtained show the mortality rate of Aedes aegypti mosquito larvae as the effectiveness of natural larvicides of Ketapang leaf extract (Terminalia Catappa).